2020
DOI: 10.1186/s12974-020-01813-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light chain and glial fibrillary acidic protein predict stroke in CADASIL

Abstract: Background: Stroke remains the most cumbersome disease burden in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). This study aimed to investigate whether plasma biomarkers can reflect disease severity and predict stroke recurrence in CADASIL patients. Methods: Sixty-three CADASIL patients (mean age 58.9 ± 9.3 years old, male 63%) from a multicenter registry and 17 controls were recruited. Plasma biomarkers, namely neurofilament light chain (NfL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Second, even in a prospective registration setting, some factors for which adjustments were necessary in the multivariable analysis may not have been adjusted. Third, we did not determine a clear cutoff value for the biomarkers for predicting outcomes, unlike several relevant studies [ 10 , 13 , 17 ]. However, variations among stroke centers in terms of patient profiles, acute treatment strategies, and standard care protocols may complicate the acquisition of a universally applicable set of values for predicting outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, even in a prospective registration setting, some factors for which adjustments were necessary in the multivariable analysis may not have been adjusted. Third, we did not determine a clear cutoff value for the biomarkers for predicting outcomes, unlike several relevant studies [ 10 , 13 , 17 ]. However, variations among stroke centers in terms of patient profiles, acute treatment strategies, and standard care protocols may complicate the acquisition of a universally applicable set of values for predicting outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a panel of single-molecule arrays focused on the CNS can simultaneously measure the levels of several biomarkers, including neurofilament light chain (NfL), glial fibrillary astrocytic protein (GFAP), tau, and ubiquitin C-terminal hydrolase L1 (UCHL1) [ 9 , 10 ]. NfL is a neuronal scaffolding protein, and its levels in cerebrospinal fluid and plasma are elevated in individuals with neurological disorders, including acute stroke [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glial fibrillary acidic protein (GFAP) is expressed in the cytoskeleton of astrocytes and has been found significantly increased in CSF in AD and other neurodegenerative diseases compared to healthy controls [12][13][14][15]. GFAP has also been recently measured in plasma and serum, where it was found increased in different neurological conditions, including AD [16][17][18][19][20][21][22][23][24]. Different studies have shown that higher concentrations of plasma GFAP were associated to amyloid-PET positivity and worse outcomes in global cognition [22,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Glial brillary acidic protein (GFAP) is expressed in the cytoskeleton of astrocytes and has been found signi cantly increased in CSF in AD and other neurodegenerative diseases compared to healthy controls (12)(13)(14)(15). GFAP has also been recently measured in plasma and serum, where it was found increased in different neurological conditions, including AD (16)(17)(18)(19)(20)(21)(22)(23)(24). Increase of plasma GFAP in AD patients was associated to amyloid-PET positivity and worse outcomes in global cognition (22,24,25).…”
Section: Introductionmentioning
confidence: 99%